Academic culture in doctoral education: are companies making a difference in the experiences and practices of doctoral students in Portugal? - Santos, P. (2021)
Aim/Purpose: This article examines the experience and practice of doctoral students by focus-ing on different dimensions of the PhD socialization process. It addresses the question of whether university collaborations with businesses influence the ex-perience and practice of PhD students. Background: The study explores the academic culture in the PhD process through the analy-sis of the experiences and practices of doctoral students in two groups - those without business collaborations (academic trajectories) and those with business collaborations (hybrid trajectories). Academic trajectories are seen as traditional academic disciplinary based doctoral education, while hybrid trajectories cross boundaries collaborating with companies in the production of new knowledge.Methodology: The article uses a qualitative methodology based on extensive interviews and analysis of the curriculum vitae of fourteen Portuguese PhD students in three scientific domains (engineering and technology sciences, exact sciences, and so-cial sciences). The doctoral program profiles were defined according to a survey applied to the directors of all doctoral programs in Portugal. Contribution: The study contributes to the reflection on the effects of collaboration with companies, in particular on the trajectories and experiences of doctoral stu-dents. It contributes to the understanding of the challenges associated with business collaborations.